Precipitation drives species accumulation whereas temperature drives species decline in Himalayan vertebrates - Yiming Hu; Luke Gibson; Huijian Hu; Zhifeng Ding; Zhixin Zhou; Weiqi Li; Zhigang Jiang; Brett R. Scheffers (Journal of Biogeography, 2022)
Aim Many studies have explored taxon‐specific richness patterns with elevation, but few have concurrently evaluated different mechanisms to explain elevational patterns across multiple taxa. We used a novel, cross‐taxa approach to study species richness patterns combined with a framework that tests drivers of species accumulation versus decline along the elevational gradient in the Himalayas. Location The Himalayas. Taxon Mammals, birds and amphibians. Methods We used geographical and elevational data of 314 mammals, 842 breeding birds and 147 amphibians to investigate species richness patterns across elevational and geographical spaces. We divided the elevational species richness gradient into segments of species accumulation versus species decline by piecewise linear regressions. We used path analysis to disentangle the direct and indirect effects of the predictors on species richness for the overall pattern and its divided segments. We test the asymmetry of main drivers between the accumulation and decline segments of richness by iteration procedure. Results Species richness for most taxa tracks an elevational hump‐shaped distribution. The dominant driver of the overall pattern varied by taxa and in context to subregion. Across taxa, precipitation best predicts the accumulation of species richness, whereas temperature best predicts the decline in species richness. Moreover, temperature and precipitation can affect species richness indirectly through productivity, showcasing a large interactional effect of climate and productivity on species richness. Main conclusions Resource allocation of the ecosystem and requirements of the species differ between the lower and upper elevation segments but remain consistent across the overall gradient. The resources essential for promoting diversity and mediating stochastic processes are directly tied to precipitation at the process of species accumulation and temperature at the process of species richness decline. Our findings support the existing theory in climate change science that reduced precipitation combined with increasing temperature may cause species extinction in the species‐rich lowlands.